Complicated appendicitis and considerations for interval appendectomy. Issue 9 (September 2018) - Perez, Kelly Sue; Allen, Steven R.
Abstract : ABSTRACT: Acute appendicitis is one of the most common surgical emergencies. Of the 300, 000 appendectomies performed each year, 25% are due to complicated appendicitis. This article reviews the incidence and pathophysiology of acute appendicitis, the nonoperative management of complicated appendicitis, and the rationales for and against interval appendectomy.